Metagenomic Insights Into Red Sea Biodiversity Across the Web of Life - Elisa Laiolo; Christopher A. Hempel; Balegh A. Abukabbos; Omar I. Abunayyan; Intikhab Alam; Taiba Alamoudi; Wejdan A. Alkhaldi; Zuhair M. Almubarak; Hamad A. Alnashri; Afrah Alothman; Tareq H. Alqahtani; Khalid A. Alshaikh; et al. (Environmental Microbiology, 2026)
Earth's biodiversity is central to ecosystem health and resilience, providing essential functions and services. The Red Sea is a recognised marine biodiversity hotspot with high endemism and unique environmental conditions that support extensive but poorly resolved biodiversity. Here, we applied metagenomic analyses to sediment samples collected from coastal to deep‐sea environments during the Red Sea Decade Expedition 2022 to characterise biodiversity across the web of life. From a single shotgun assay per sample, this approach simultaneously characterised the sediment microbiome, which amplicon‐based surveys recover only through parallel, targeted assays, and extended detection to higher eukaryotes. Using high‐throughput sequencing, we generated 12.8 billion sequences, revealing taxa covering all domains of life. Although eukaryotic sequences represented only 0.7% of the taxonomically annotated dataset, we managed to identify 679 eukaryotic families. Prokaryotic diversity was high, as expected in a basin‐scale sampling coupled with high sequencing depth, with groups covering a wide functional array. Community structure analyses revealed depth‐driven stratification of open‐ocean benthic microbial communities and latitudinal structuring of coastal benthic eukaryotes. Overall, this dataset provides an empirical reliability–coverage trade‐off with direct consequences for the design of eDNA monitoring programmes targeting conservation‐priority taxa, and clear priorities for taxa specific reference‐database expansion.

First application of quantitative fatty acid signature analysis in bottlenose dolphins (Tursiops truncatus) and its implications for diet estimation in free-ranging cetaceans - Theresa-Anne M. Tatom-Naecker; Suzanne M. Budge; Celeste B. Parry; Stephen J. Trumble; Randall S. Wells; Daniel P. Costa (Frontiers in Marine Science, 2026)
Introduction Quantitative fatty acid signature analysis (QFASA) can provide species level diet estimates integrated over weeks to months, which are valuable for assessing health, ecological roles, and disturbance vulnerability. However, the approach has seen limited use in cetaceans. Calibration coefficients (CCs) have mainly been derived from non-cetacean mammals, best-fit QFASA model parameters are undefined, and the temporal integration of blubber fatty acids (FAs) remains poorly resolved. Method We used bottlenose dolphins ( Tursiops truncatus , n = 3, hereafter "dolphin") under professional care with known, varied diets to develop and evaluate species- and blubber layer-specific CCs and explore model performance under different parameter combinations. For each dolphin, we calculated CCs for the inner and outer blubber, compared these to published non-dolphin CCs, and evaluated QFASA-estimated diets across different FA sets, distance measures, CC sources (dolphin and non-dolphin), and FA integration periods. Model performance was assessed using prey distinctiveness, the percentage of predator FAs that fell outside prey ranges [predator-beyond-prey (PBP) values], and weighted error between estimates and the dolphins’ known diets. Results Dolphin CCs differed between the inner and outer blubber and from non-dolphin CCs for many FAs. Dolphin-specific, layer-matched CCs produced lower-error estimates and identified key prey species more accurately than non-dolphin CCs. Inner and outer blubber estimates were consistent with prey consumption integrated over weeks to months, supporting QFASA’s long-term nature. However, model performance was sensitive to FA set, distance measure, CC source, and dolphin diet complexity. In some parameter combinations, the augmented FA contributed a large portion of the model signal, reducing interpretability. This highlights the need for cautious parameter selection. Discussion These results provide the first layer-specific CCs for bottlenose dolphins and illustrate the utility and limitations of QFASA for cetacean diet estimation. We recommend that investigators use species- and layer-specific CCs where possible and consider prey distinctiveness, PBP values, and the augmented FA’s contribution when selecting model parameters. We also caution against over-interpreting best-fit parameter sets and diet estimates derived from small calibration datasets. To yield the most complete understanding of free-ranging cetacean diet, QFASA is best applied as one of several complementary methods rather than as a standalone approach.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Associations between immunological and hormonal parameters during healthy pregnancy in mares - Lorena S. Feijo; Joy Ledeck; Karen Wolfsdorf; Jerome Ponthier; Stephen Parry; M. Julia B. Felippe (Theriogenology, 2026)

Biodegradation of 2,4,6-trinitrotoluene by Biofilm Forming and Plant Growth Promoting Burkholderia gladioli: An Approach Towards Degradation Pathway Prediction - Aditya Roy; Urvi Santosh Mhadeshwar; Parry Dey; S. Mary Celin; Dipti B. Bose; Arvind Kumar; W. Jabez Osborne (Water, Air, & Soil Pollution, 2026)

The Relationship Between Perceived Discrimination and Reported Nutrient Intake Among Pregnant Individuals of Minoritized Racial and Ethnic Groups - Tatyana Johnson; Ann K. Kan; Lauren B. Bonner; Linda Van Horn; Kiarri N. Kershaw; William A. Grobman; Karen L. Lindsay; Michelle P. Debbink; Brian M. Mercer; David M. Haas; George R. Saade; Uma Reddy; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Application of blood parameters for the early diagnosis of natural ascending placentitis in pregnant mares - Lorena S. Feijo; Karen E. Wolfsdorf; Igor F. Canisso; Stephen Parry; M. Julia B. Felippe (Theriogenology, 2024)

An insight on the plausible biological and non-biological detoxification of heavy metals in tannery waste: A comprehensive review - Parry Dey; Jabez W. Osborne; Kirubhadharsini B. Lincy (Environmental Research, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Double outlet right atrium in a dog - F. Sarcinella; B. Pedro; S. Sudunagunta; A. Parry; S. Swift (Journal of Veterinary Cardiology, 2024)

Red Pigmentation Can Be Used to Reliably Distinguish Between Live Calanus finmarchicus and Calanus glacialis Females in the Fram Strait - Penelope K. Lindeque; Isabelle Hann; Helen E. Parry; Kathryn B. Cook; Anthony J. W. Lindley; Daniel J. Mayor (Frontiers in Marine Science, 2022)
Copepods from the genus Calanus provide an important lipid-rich food source in the Arctic marine foodweb. Despite extensive research on Calanus finmarchicus and Calanus glacialis , accurately identifying adults to species level remains challenging due to similar morphologies. Although these species co-occur in many regions, the distribution of C. finmarchicus and C. glacialis correspond to Atlantic and Arctic water masses respectively and are frequently used as climate indicators. Correct identification is therefore vital for understanding the phenotypic plasticity of these species and the impacts climate change will have on Calanus- dominated marine ecosystems. In this study, prosome length and percentage of red pigmentation (redness) of genital somites, the antennae, and throughout the whole body were determined for 139 females of C. finmarchicus and C. glacialis from the Fram Strait. Molecular analysis of a 16S rDNA barcode confirmed that the best morphological features for resolving the identity of these two species were the redness of the antennae and the redness of the genital somites. Overall accuracy of using antennae redness and genital somite redness to discriminate between the two species were the same, yet each of these explanatory variables had different specificity; C. finmarchicus were more accurately identified by the absence of redness in the genital somites, whereas C. glacialis were more accurately identified using antennae redness. Given the ecological importance of these congeners, these findings contribute to a better understanding of the reliability of using morphological characteristics to identify Calanus to species level, especially when sorting live specimens for climate-related ecological experiments.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Can a key boreal Calanus copepod species now complete its life-cycle in the Arctic? Evidence and implications for Arctic food-webs - Geraint A. Tarling; Jennifer J. Freer; Neil S. Banas; Anna Belcher; Mayleen Blackwell; Claudia Castellani; Kathryn B. Cook; Finlo R. Cottier; Malin Daase; Magnus L. Johnson; Kim S. Last; Penelope K. Lindeque; et al. (Ambio, 2022)
The changing Arctic environment is affecting zooplankton that support its abundant wildlife. We examined how these changes are influencing a key zooplankton species, Calanus finmarchicus , principally found in the North Atlantic but expatriated to the Arctic. Close to the ice-edge in the Fram Strait, we identified areas that, since the 1980s, are increasingly favourable to C. finmarchicus . Field-sampling revealed part of the population there to be capable of amassing enough reserves to overwinter. Early developmental stages were also present in early summer, suggesting successful local recruitment. This extension to suitable C. finmarchicus habitat is most likely facilitated by the long-term retreat of the ice-edge, allowing phytoplankton to bloom earlier and for longer and through higher temperatures increasing copepod developmental rates. The increased capacity for this species to complete its life-cycle and prosper in the Fram Strait can change community structure, with large consequences to regional food-webs.

Comparisons of Serum Progesterone and Progestagen Concentrations in Normal and Abnormal Bottlenose Dolphin (Tursiops truncatus) Pregnancies - Todd R. Robeck; Karen J. Steinman; Celeste B. Parry; Forrest M. Gomez; Eric D. Jensen (Frontiers in Marine Science, 2021)
Although previous studies have described progesterone profiles during pregnancy in the bottlenose dolphin ( Tursiops truncatus ), most of these focused on normal pregnancy (NORM) or compared NORM to only one or two abnormal pregnancy types, such as abortion (AB) or perinatal loss (PNL). Hormonal pregnancy biomarker analysis from reproductive events with different outcomes may reveal differences in concentrations so that we are able to identify high risk pregnancies. The aim of this study was to describe longitudinal profiles of circulating progesterone and progestagens during reproductive events in the female bottlenose dolphin, including NORM, failure to thrive, PNL, AB, early loss (EL), and false pregnancy (FP). Progesterone differed from NORM during EL at EARLY (month post conception [MPC] 1–4), AB at MID (MPC 5–8), and FP at LATE (MPC 9–12) stages. Progestagens differed from NORM during AB and FP at MID and LATE stages and during MPC 12 in PNL and MPC 4 in EL. Progestagens may be better at predicting poor reproductive outcome in the bottlenose dolphin and a suite of hormone tests, including progesterone and progestagens, should be incorporated into existing clinical diagnostic and management practices in this species. Furthermore, analysis of multiple hormonal pregnancy biomarkers from a single sample may enable pregnancy diagnosis for wild animals.

Do community-level models account for the effects of biotic interactions? A comparison of community-level and species distribution modeling of Rocky Mountain conifers - Paige E. Copenhaver-Parry; Shannon E. Albeke; Daniel B. Tinker (Plant Ecology, 2016)

The cost‐effectiveness of biodiversity surveys in tropical forests - Toby A. Gardner; Jos Barlow; Ivanei S. Araujo; Teresa Cristina Ávila‐Pires; Alexandre B. Bonaldo; Joana E. Costa; Maria Cristina Esposito; Leandro V. Ferreira; Joseph Hawes; Malva I. M. Hernandez; Marinus S. Hoogmoed; Rafael N. Leite; et al. (Ecology Letters, 2008)
The identification of high‐performance indicator taxa that combine practical feasibility and ecological value requires an understanding of the costs and benefits of surveying different taxa. We present a generic and novel framework for identifying such taxa, and illustrate our approach using a large‐scale assessment of 14 different higher taxa across three forest types in the Brazilian Amazon, estimating both the standardized survey cost and the ecological and biodiversity indicator value for each taxon. Survey costs varied by three orders of magnitude, and dung beetles and birds were identified as especially suitable for evaluating and monitoring the ecological consequences of habitat change in our study region. However, an exclusive focus on such taxa occurs at the expense of understanding patterns of diversity in other groups. To improve the cost‐effectiveness of biodiversity research we encourage a combination of clearer research goals and the use of an objective evidence‐based approach to selecting study taxa.

Within-field variability of Fusarium head blight pathogens and their associated mycotoxins - X.-M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Predominance and association of pathogenic fungi causing Fusarium ear blightin wheat in four European countries - X. -M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; J. M. Brennan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2005)

The Consequences of CO2 Stabilisation for the Impacts of Climate Change - N. W. Arnell; M. G. R. Cannell; M. Hulme; R. S. Kovats; J. F. B. Mitchell; R. J. Nicholls; M. L. Parry; M. T. J. Livermore; A. White (Climatic Change, 2002)

Ultrastructural localization of relaxin in the corpus luteum of the pregnant and early lactating tammar wallaby, Macropus eugenii - Laura J. Parry; Joan M. Clark; Marilyn B. Renfree (Cell and Tissue Research, 1997)